1996
DOI: 10.1074/jbc.271.25.14740
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na+/Glucose Cotransporter Expression by Protein Kinases in Oocytes

Abstract: Cotransporters are proteins responsible for the accumulation of nutrients, neurotransmitters, and drugs in cells. As forskolin has been shown to stimulate intestinal Na+/glucose cotransport, we have used electrophysiological techniques to examine the role of protein kinases in regulating Na+/glucose cotransporters, SGLT1, expressed in Xenopus laevis oocytes. We monitored SGLT1 kinetics, the number of SGLT1 cotransporters in the plasma membrane, and plasma membrane area before and after activation of protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
153
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 29 publications
14
153
1
1
Order By: Relevance
“…Whether additional posttranslational modification is required before SGLT2 expresses in oocytes is uncertain. An important role of protein kinases for sodium-glucose co-transporters has been demonstrated for SGLT1, and it has been suggested that despite that SGLT show high sequence homology, minor differences in amino acid sequence may dramatically change the regulation of trafficking by protein kinases (36). The ultimate reason for poor expression of SGLT2 in heterologous systems, however, has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether additional posttranslational modification is required before SGLT2 expresses in oocytes is uncertain. An important role of protein kinases for sodium-glucose co-transporters has been demonstrated for SGLT1, and it has been suggested that despite that SGLT show high sequence homology, minor differences in amino acid sequence may dramatically change the regulation of trafficking by protein kinases (36). The ultimate reason for poor expression of SGLT2 in heterologous systems, however, has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of the Na ϩ -D-glucose co-transporter molecules in the plasma membrane may be changed within minutes via endo-and exocytosis (14). In contrast, the transcriptional regulation of SGLT1 is known to occur more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of SGLT1 has been studied in small intestine (7,(11)(12)(13), in Xenopus oocytes (14), and in the renal epithelial cell line LLC-PK 1 which is derived from porcine kidney proximal tubule cells (15)(16)(17)(18)(19)(20)(21)(22). One of the factors that affect the expression of SGLT1 in small intestine and LLC-PK 1 cells is extracellular D-glucose concentration (7,17,18).…”
mentioning
confidence: 99%
“…including cytosol to membrane recycling in oocytes, 66 intestinal GLUT2 recruitment, 67 and translocation of GLUT1 in retinal capillary membranes 68,69 and mesangial cells. 70 PKC also regulates translocation of GLUT1 71 and GLUT4 in muscle 72,73 and fat cells.…”
Section: Figmentioning
confidence: 99%